That’s our code : a feminine artistic encoding of memories of the South African Defence Force between 1977 and 1989 and hegemonic masculinity in white South African men - Sooful, Avi (University of Pretoria, 2024)
Mini Dissertation (MA (Fine Arts))--University of Pretoria, 2023.